(untitled) - McRae, Hamish (Boston, Mass., 1995)
In the year 2020, all having embraced market capitalism, the North American, European and East Asian countries will be engaged in fierce economic competition. With each nation increasingly able to imitate the others, innovations will cross borders within more days and weeks, removing technological prowess as a source of sustained advantage.
Keywords: Thế kỷ 21,Twenty-first century; Dự báo,Forecasts